Penerapan Media YouTube terhadap Hasil Belajar Peserta Didik Pada Materi Telling the Time kelas VII - Fitrah, Aenul (Indonesian Journal of Pedagogical and Social Sciences, 2023)
Abstract. The purpose of this research is to determine the use of learning media Youtube for teaching telling the time subject to class VII A students at SMP Negeri 6 Watampone, and to observe whether there is an improvement in students' learning outcomes. This research adopts the Classroom Action Research (CAR) method. The research stages include planning, action implementation, observation, and reflection. The research subjects in this study are all 28 students of class VII A. The data were analyzed thematically, and the findings revealed that the use of engaging YouTube learning videos positively influenced students learning outcomes. The research findings indicate an improvement in students' learning outcomes and their engagement during the learning process. Each research cycle shows improvement, with the average score in the initial assessment of 70.00 increasing to 88.00 in the final assessment. Based on these results, it is recommended that teachers implement innovative teaching models and utilize learning media. The utilization of instructional videos on YouTube needs to be optimized to enhance students' learning outcomes. Keywords: Learning Media, Youtube, Student Learning Outcomes